Combination of Entrapment and Covalent Binding Techniques for Xylanase Immobilisation on Alginate Beads: Screening Process Parameters - Siti Sabrina, Mohd Sukri; Mimi Sakinah, A. M. (sociation of Chemical Engineering - AIDIC, 2017)
Xylanase are responsible enzyme for hydrolysis of xylan into many beneficial products such as xylose, xylitol and xylooligosaccharides. Due to industrial potential of xylanase, a large number of studies have become interested in their immobilisation to reduce the cost of enzyme. Immobilised enzymes are currently the object of interest due to its benefits over soluble or free enzyme applied in enzymatic hydrolysis. The aims of this study were to determine the suitable method for xylanase immobilisation and to identify the significant parameter which affecting the immobilisation yield by fractional factorial design (FFD). Immobilised xylanase was prepared using a single immobilisation techniques of entrapment and covalent binding and also a combination of entrapment and covalent binding techniques. The immobilisation conditions for xylanase which includes of sodium alginate concentration, calcium chloride concentration, agitation rate and enzyme loading were screened using FFD experimental design to determine the most significant parameters in affecting the efficiency of immobilised xylanase. The analysis of xylanase activity was determined using dinitrosalicyclic acid (DNS) method. The xylanase enzyme was successfully immobilised by entrapment in sodium alginate beads and covalent binding on the surface of beads by glutaraldehyde. The combination of entrapment and covalent binding showed the highest immobilisation yield of 65.81 % compared to a single technique which contributes only 31.99 % and 48.53 %. Glutaraldeyhde concentration showed the most significant parameters compared to the others parameter which gives about 69.01 % of contribution on the xylanase immobilisation yield. The study shows the efficiency of enzyme immobilisation could be improved by a combination of immobilisation techniques and determination of the most significant factors for xylanase immobilisation.